2007
DOI: 10.1021/ie0702328
|View full text |Cite
|
Sign up to set email alerts
|

Change of CO2Carrying Capacity of CaO in Isothermal Recarbonation−Decomposition Cycles

Abstract: The change of CO2 carrying capacity of CaO sorbents prepared from different precursors has been studied using thermogravimetric analysis in a long series of isothermal recarbonation−decomposition cycles in the temperature range of 750−850 °C. The residual capacity of the CaO sorbents after a large number of cycles was found to depend on the precursor type, the experimental temperature, and the duration of the recarbonation stage. The residual capacities of the CaO derived from the powdered calcium carbonates w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
215
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(229 citation statements)
references
References 20 publications
(35 reference statements)
14
215
0
Order By: Relevance
“…Such findings are consistent with those of (Lysikov et al, 2007) and confirmed by (Manovic and Anthony, 2008) who demonstrated that pre-sintering limestones by heating them to a high temperature (> 1200 °C ) for long periods of time (up to 24 h), though initially causing significant sintering and loss of reactivity, led to an increase in the long-term reactivity of the limestones. It was hypothesised (Lysikov et al, 2007) that rapid initial sintering of the sample led to the formation of a hard internal skeleton of an optimal pore-size distribution which acted as a support for subsequent cycles of carbonation and calcination.…”
Section: Resultssupporting
confidence: 90%
“…Such findings are consistent with those of (Lysikov et al, 2007) and confirmed by (Manovic and Anthony, 2008) who demonstrated that pre-sintering limestones by heating them to a high temperature (> 1200 °C ) for long periods of time (up to 24 h), though initially causing significant sintering and loss of reactivity, led to an increase in the long-term reactivity of the limestones. It was hypothesised (Lysikov et al, 2007) that rapid initial sintering of the sample led to the formation of a hard internal skeleton of an optimal pore-size distribution which acted as a support for subsequent cycles of carbonation and calcination.…”
Section: Resultssupporting
confidence: 90%
“…A reasonable agreement between the calculated trend of conversion and some of the experimental data reported by Manovic et al [17] was accomplished [24]. Further agreement with experimental data obtained by Barker [10] and Lysikov et al [29] for prolonged carbonation periods was reported elsewhere [8]. Following the model, the conversion of a sorbent which is allowed to react under the diffusion-controlled regime would finally tend to the same apparent residual activity than the nonpretreated sorbent independently of the conditions of thermal pretreatment [24].…”
Section: Models On Multicyclic Cao Conversionsupporting
confidence: 77%
“…The time of sintering would scale thus proportionally to the number of cycles t ∝ N and the residual conversion X r is introduced as an empirical parameter. Lysikov et al [29] proposed an alternative view according to which CaO multicyclic conversion stabilizes at a residual value after a large number of recarbonation/decomposition cycles due to the formation of an interconnected…”
Section: Models On Multicyclic Cao Conversionmentioning
confidence: 99%
“…It has been reported that the higher calcination temperature markedly accelerated the sintering of CaO [29], which decreased the CO 2 capture capacity [30]. Therefore, it was expected that the CO 2 capture capacity of the 500-Ca4 catalyst would be the highest in our prepared catalysts, enhancing the in situ CO 2 absorption.…”
Section: Influence Of the Ca Content And Calcination Temperature On Tmentioning
confidence: 89%